Post disaster housing reconstruction framework for flood victims: Lokoja, Kogi State, Nigeria - Ahmodu, Adaji Adejah (2019)
The Nigerians States in 2012 experienced an unprecedented flood in areas of high risk among which Kogi State is the worst hit. In response to the havoc wreaked on the people and built environment by these floods, Kogi State government embark on post-disaster housing reconstruction (PDHR) projects which are supposed to give succor to the beneficiaries and better their lives. However, its failure has been imminent due to inadequate attention given to vital strategies contributing to the effectiveness of reconstruction strategies in Nigeria. Objectives of the study were to investigate the current community involvement in PDHR, identify community perception on PDHR, assess the impacts of the identified vital strategies on PDHR, and propose and validate PDHR framework for flood victims in Lokoja, Nigeria. The study approach was quantitative. Simple random sampling was used to administer structured questionnaires to a total of 400 houses, out of which 257 valid questionnaires constituting 64% from the population of 2012 flood victims at Lokoja metropolis, Nigeria was used in the analysis. The data was analysed using Statistical Package for Social Science (SPSS) version 21 and Partial Least Squares Structural Equation Modelling Software, SmartPLS 3.0. Results showed that community involvement in the housing reconstruction is insignificant especially in risk assessment and flood information gathering (1.94), collaboration with the community (1.80), and the consequence was dissatisfaction with the reconstruction process (1.96), and reconstructed houses (2.18). The models revealed that the identified strategies jointly explained about 26.6% of the variance in effective PDHR. Furthermore, mediation analysis showed that community satisfaction with reconstruction strategies mediated adequately (T-value=2.413 and P-value=0.016; T-value=2.075 and P-value=0.038). Therefore, the study concluded with emphasis on the importance of community involvement in the identified strategies as it will significantly influence beneficiaries’ satisfaction and perception on PDHR projects. Moreover, it will add value to the reconstruction process and reconstruction products thereby enhancing the sustainability of the projects and provide a disaster resilient community in Nigeria. Based on that, a PDHR framework for flood victims in Nigeria was proposed and then validated by appropriate stakeholders.